2007
DOI: 10.1002/acp.1400
|View full text |Cite
|
Sign up to set email alerts
|

The role of recipient perspective in giving and following wayfinding directions

Abstract: We examined how recipient perspective and descriptive features affect direction giving and following during wayfinding. In Experiment 1, participants provided directions from starting locations to destinations for fictional recipients driving through a town (route perspective) or looking at a map of the town (survey perspective). As expected, participants included left-right and landmarks more frequently when addressing a person driving in the town and cardinal descriptors more frequently when addressing a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 65 publications
3
22
1
Order By: Relevance
“…dressees are driving in the environment or looking at their maps (Hund et al 2008). The findings from the current study suggests that in signed language descriptions, when an addressee is present, the signers do not change their perspectives contra to what English speakers can do.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…dressees are driving in the environment or looking at their maps (Hund et al 2008). The findings from the current study suggests that in signed language descriptions, when an addressee is present, the signers do not change their perspectives contra to what English speakers can do.…”
mentioning
confidence: 70%
“…Hund et al (2008) studied whether the describers change their perspectives when giving directions to the addressees. They found that the describers use egocentric terms such as left-right and landmarks more frequently when the addressees driving in the town and use cardinal directions such as north-south more frequently when the addressees looking at a map.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research has focused on comparisons of Western and non-Western cultures. In contrast, US and European studies investigating flexibility of spatial descriptions and recipient perspectives largely have ignored cultural factors (e.g., Brunyé & Taylor, 2008;Hund, Haney, & Seanor, 2008;Noordzij & Postma, 2005;Pazzaglia, Meneghetti, DeBeni, & Gyselinck, 2010;Taylor & Tversky, 1992). As such, the primary goal of this investigation was to determine how culture and recipient perspective affect direction giving in the service of wayfinding.…”
Section: Introductionmentioning
confidence: 87%
“…The most suitable representation is a function of the information which requires representation. If one wishes to represent information regarding segments of the route which would be encountered during navigation, commonly referred to as a route perspective [24], a linguistic or augmented-reality representation is most suitable. On the other hand if one wishes to represent information regarding an overview of the environmental layout, commonly referred to as a survey perspective [24], a map or sketch representation is most suitable.…”
Section: Route Descriptions -Information and Representationmentioning
confidence: 99%
“…Dennis et al [14] found that linguistic descriptions which were clear, complete and containing an adequate number of landmarks, but without redundancy or uncertainty, were rated highly. Hund et al [24] asked individuals to state their individual preferences regarding linguistic descriptions. Individuals responded positively to landmark and left-right information and negatively to cardinal directions.…”
Section: Route Descriptions -Information and Representationmentioning
confidence: 99%